2021
DOI: 10.1109/tifs.2021.3067998
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Task-Independent Person-Specific Signatures in EEG Using Subspace Techniques

Abstract: Electroencephalography (EEG) signals are promising as alternatives to other biometrics owing to their protection against spoofing. Previous studies have focused on capturing individual variability by analyzing task/condition-specific EEG. This work attempts to model biometric signatures independent of task/condition by normalizing the associated variance. Toward this goal, the paper extends ideas from subspace-based textindependent speaker recognition and proposes novel modifications for modeling multi-channel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Hence, the success of the single-channel SSVEP-based biometric approach for 11 people may have been dependent on this implemented task. By using 12 and 15 Hz in our approach, the suggested frequency range (12)(13)(14)(15)(16)(17)(18) to provide maximum accuracy for BCI applications was included [40]. Furthermore, multi-channel recordings were also addressed and found to be helpful in capturing the high flickering frequencies as SSVEP responses [40].…”
Section: Bidirectional Models and Gated Recurrent Unitmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the success of the single-channel SSVEP-based biometric approach for 11 people may have been dependent on this implemented task. By using 12 and 15 Hz in our approach, the suggested frequency range (12)(13)(14)(15)(16)(17)(18) to provide maximum accuracy for BCI applications was included [40]. Furthermore, multi-channel recordings were also addressed and found to be helpful in capturing the high flickering frequencies as SSVEP responses [40].…”
Section: Bidirectional Models and Gated Recurrent Unitmentioning
confidence: 99%
“…Hence, these features can make the SSVEP a highly potential candidate for structuring real-time usage in human-computer interfaces consisting of biometric applications [10,11]. A great number of EEG-based and VEP-based biometric studies dealing with multi-trial and multi-channel recordings can be found in the literature [13][14][15][16][17][18][19]. However, few studies are based on the single-channel dry-electrode SSVEP approach with single-trial person identification [9,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the fact that the number of electrodes has been effectively reduced, the application in reengineering remains inconvenient. In 2021, Mari Ganesh Kumar et al [30] proposed the best subspace approach (ix-vector) to identify persons with an accuracy of 86.4 % with only 9 EEG channels. In 2022, Chiqin Lai [31]proposed a CNN combined with an error correcting output code of support vector machine with majority voting set (CNN-ECOC-SVM) for biometric recognition showing that 98.49 % accuracy was achieved in the proposed architecture.…”
Section: Comparison With Related Workmentioning
confidence: 99%
“…The electroencephalogram is produced by inducing an electric field on the subject's scalp, the characteristics of which are determined by the firing of spatially arranged cortical pyramidal neurons, and this brain activity is typically classified into five distinct oscillatory rhythms [5], namely delta (0.5-4 Hz), theta (4-8 Hz), alpha (8)(9)(10)(11)(12)(13), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and gamma (≥ 30 Hz). The characteristics of EEG signals are unique and enduring aspects of the brain, and compared to conventional biometric identification, EEG signals offer more visible benefits [6]: (i) High concealment: EEG signals are generated within the brain, necessitating the need for a specialized acquisition instrument; (ii) Liveness detection: creation of EEG signals must ensure owner activity in the area where they are placed, and EEG signals will vanish when the owner dies; (iii) Difficult to harm [7]: Compared to fingerprints, faces, and other biometric features that are exposed to the outside world for an extended period of time, the EEG is contained within the head and is the most vital and well-protected organ, which ensures that the EEG signal can be used as a biometric authentication without fear of causing damage to the EEG or allowing it to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Projection of high-dimensional data into a lower-dimensional space is proposed in the literature to overcome the large data size problem [59]. Kumar et al [61] proposed a new approach for modelling multi-channel EEG data as biometric signatures regardless of task/condition by using the fundamentals of subspace-based text independent speaker verification. They applied the high dimensional statistics EEG signals, then projected them into a lower dimensional subspace.…”
Section: Introductionmentioning
confidence: 99%